Differences in serum IL-6 response after 1 °C rise in core body temperature in individuals with spinal cord injury and cervical spinal cord injury during local heat stress. (31st December 2018) - Hashizaki, Takamasa; Nishimura, Yukihide; Teramura, Kenzo; Umemoto, Yasunori; Shibasaki, Manabu; Leicht, C. A.; Kouda, Ken; Tajima, Fumihiro
Abstract: Objectives: Passive rise in core body temperature achieved by head-out hot water immersion (HHWI) results in acute increases in serum interleukin (IL)-6 but no change in plasma adrenaline in patients with cervical spinal cord injury (CSCI). The purpose of the present study was to determine the mechanism of heat stress-induced increase in serum IL-6. Setting: A cross-sectional study. Methods: The study subjects were nine with CSCI, ten with thoracic and lumbar spinal cord injury (TLSCI) and eight able-bodied (AB) subjects. Time since injury was 16.1 ± 3.4 years in TLSCI and 16.4 ± 4.1 years in CSCI. Subjects were subjected to lower-body heat stress (LBH) by wearing a hot water-perfused suit until 1 °C increase in core temperature. The levels of serum IL-6, plasma adrenaline, tumour necrosis factor (TNF)-α, C-reactive protein (CRP), and counts of blood cells were measured at normothermia and after LBH. Results: Serum IL-6 concentrations increased significantly immediately after LBH in all the three groups. ΔIL-6% was lower in CSCI subjects compared with AB subjects. Plasma adrenaline concentrations significantly increased after LBH in AB and TLSCI subjects, but did not change throughout the study in CSCI subjects. Cardiac output and heart rate increased at the end of LBH in all three groups. Conclusions: Under a similar increase in core temperature, ΔIL-6% was lower in the CSCI group compared with the AB group. These findings suggest that the observed rise in IL-6 during hyperthermia is mediated, at least in part, by plasma adrenaline.